Mencari Pengobatan Tradisional di Desa Simatibung, Kecamatan Laguboti, Kabupaten Toba - Robecca Evamelenium Sinaga; A.A.N. Anom Kumbara; I Gusti Putu Sudiarna (Department of Anthropology Udayana University, 2023)
This study discusses about the behavior of the Simatibung Village community in seeking of alternative or traditional medicine. In this study, the author using an ethnographic method with the theory of Health Belief Model and Health Seeking Behavior. From the data that has been obtained, there are several factors that influence the behavior of the Simatibung Village community, ranging from access, economy to trust, from these indicators people tend to choose traditional medicine than modern medicine in health centers.